Design & Development of Soundable CYO. Issue 4 (May 2019) - Zhan, Jianbo; Zheng, Han; Wang, Hao; Xie, Jiao; Yu, Tingting; Yue, Baoshan; Wang, Xu; Li, Geng; Yu, Zhenhua; Zhang, Ying; Wang, Tao; Yu, Jiang; et al.
Abstract: In order to increase the interest of cigarette smoking, enrich consumers' consumption experience, realize the satisfaction of hearing in the process of cigarette combustion, and meet the needs of some consumers who have little warning effect on hearing sound, a sound-producing CYO component was designed and produced, which uses the sound-producing device to be installed between the upper cover and the lower cover of the connector, so that the sound-producing mode of the connector adopts pure mechanical structure to achieve. The physical parameters of the splicer are calculated by ANSYS software, and the connecting effect is simulated. The CYO cigarettes connected by the connector are verified. The results show that the connector achieves the sticky effect and the tightness similar to the conventional cigarettes. There is no significant difference between smoking evaluation and smoke detection with conventional cigarettes, thus the ideal design effect is achieved.